Influence of large-scale structures on the stability of the hangingwall in a caving mine: a modelling study - Umar, Sraj Banda; Edelbro, Catrin (International Journal of Mining and Mineral Engineering, 2016)
The Printzsköld orebody in the Malmberget mine of NorthernSweden is currently under production and is centrally located in the miningarea. The effects of the on-going sublevel cave-mining in this orebody arecurrently investigated with respect to cave development with an initialemphasis on the effects of stress redistribution and potential rock massyielding. In this study, three-dimensional discontinuum modelling of thePrintzsköld orebody is presented, in which the effect of three pre-existinglarge-scale geological structures have been studied. The results of the presentstudy showed low stress build-ups in the crown pillar and cave bottom, due toshear slip developing along the structures. The presence of large-scalestructures has no significant effects on the far-field stresses as shear slip alongthese structures is confined to cave boundaries. An analysis of the shearstrength of the structures showed larger effects of slip on reducing frictionangle than the reduction of cohesion. Funder: Hjalmar Lundbohm Research Centre (HLRC)